A rapid and simple endoscopic resection of gastric fundus submucosal tumors - Mingwen Guo; Bing Yang; Yi Juan Guo; WenGuang Yang; SiChao Wen; YuHong Ren (DEN Open)
Abstract A 56‐year‐old male patient was diagnosed with a submucosal tumor in the fundus of the stomach. The conventional operation method is endoscopic submucosal dissection. We present a case of rapid tumor resection without employing traditional endoscopic submucosal dissection instruments such as a mucotomy knife and endoscopic injection needle, resulting in substantial cost savings for the patients.